The Use of Local Character's Biography to Build Nationalism and Patriotism - Rajilun, Mus (International Journal Pedagogy of Social Studies, 2019)
Nationalism and patriotism are two of the required characters which must be owned by individual or individual as a part of a society. Nowadays, there is an undeniable fact that our children, especially those in the junior and senior high schools, love more foreign characters (idols and heroes) rather than loving their national characters that fought for this land, Indonesia. There are many ways to teach history in order to build nationalism and patriotism characters of the students. One of the ways is by using biography. By involving 41 students of social science and 2 history teachers in a senior high school, this natural inquiry study shows that the biography of local character (local hero) can build the students’ nationalism and patriotism with some noticeable challenges in the practice.